Job-satisfaction in the broader framework of the capability approach - Ortrud Leßmann; Jean-Michel Bonvin (Management Revue, 2011)
Being one of the leading paradigms for analyzing human well-being, the Capability Approach (CA) may serve as a frame of reference for job-satisfaction. The CA mainly argues for (1) complementing information on job-satisfaction by the more objective conception of valuable work to avoid biases due to adaptive preferences and (2) taking a holistic perspective of the multidimensional work-situation while (3) emphasizing the importance of opportunities and individual choice and agency. Thereby the CA provides a new perspective on classical insights on job-satisfaction by putting them into a broader framework. This paper is but a first tentative appreciation of the CA in this context.
Keywords: D63; J28; M52; 650; job-satisfaction; valuable work; capability approach; subjective well-being; participation